The Seven Sorrows Confraternity of Brussels (Brepols, 2025)
Devotion to the Virgin of Seven Sorrows flourished in the Low Countries in the late fifteenth and early sixteenth centuries under the auspices of the court of Philip the Fair. Quickly becoming a widespread phenomenon, the Seven Sorrows devotion generated dramatic plays, artistic works, music, and numerous miracles. Underlying the popularity of the devotion was the network of confraternity chapters dedicated to the Virgin of Sorrows. Of these chapters, the Seven Sorrows confraternity of Brussels was singled out, receiving the special patronage of Philip the Fair, Maximilian I, and Margaret of Austria. Taking the confraternity of Brussels as a focal point, this volume examines the Seven Sorrows devotion in its urban context. The essays of this collection explore the artistic, musical, and dramatic products of the Seven Sorrows devotion as created in and by the civic networks and artistic channels of Brussels. The structure of the confraternity and its historical importance for the city are also demonstrated. As an important counterpoint to work in Italian confraternity studies, this volume is the first interdisciplinary study of a confraternity in the Low Countries in English.